Analiza merilnih sistemov za zagotavljanje kakovosti v procesu šest sigm - Soković, Mirko (Strojniški vestnik, 2005)
To maintain market share, suppliers to the automotive industry must be involved in the continuous improvement of their processes. They have to strive to perfect their processes as well as their overall business. Therefore,the search for appropriate improvement methods is ongoing, whether these methods are well known or completely new, e.g., six-sigma (6s) methods. This paper explains the analysis of measuring systems as a part of a six-sigma methodology.
Keywords: sistemi merilni; variacije; variation; metodologija šest sigem; analize R and R; merilni sistemi; zagotavljanje kakovosti; šest sigm